Mobility in the English novel from Defoe to Austen - Ewers, Chris (Boydell Press, 2018)
A lively exploration of the relation between the arrival of the novel, the literary form that uses life-as-a-journey as its master trope, and the transport revolution in eighteenth-century Britain.